Integrating Ethics with Psychiatry. The case of Antoni Kępiński - Łuków, Paweł (Acta Universitatis Lodziensis. Folia Philosophica. Ethica-Aesthetica-Practica, 2016)
This paper argues that in the case of mental illnesses whose somatic bases are not known or do not exist, a promising route to understand mental illness is to see it as the lack of a patient’s engagement with some moral values that are necessary for a good human life. The paper explains how the first-person perspective, which is constitutive for mental illnesses, makes it impossible to provide an adequate, third-person explanation of the pathological. Because of its irreducible first-personal nature, mental illness must be understood (also) in terms of a moral harm to the patient, and so an integration of ethics and psychiatry (at least at the level of practice) is required. This view is further illustrated with A. Kępiński’s idea of psychiatry as therapy with moral values.